2011
DOI: 10.1093/infdis/jir633
|View full text |Cite
|
Sign up to set email alerts
|

C21orf91 Genotypes Correlate With Herpes Simplex Labialis (Cold Sore) Frequency: Description of a Cold Sore Susceptibility Gene

Abstract: We evaluated candidate genes in the cold sore susceptibility region using fine mapping with 45 SNP markers. 2 complementary techniques identified C21orf91 as a gene of interest for susceptibility to HSL. We propose that C21orf91 be designated the Cold Sore Susceptibility Gene-1 (CSSG1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 26 publications
1
36
1
1
Order By: Relevance
“…We reported that a series of polymorphic key regulators at the interface of innate and adaptive immunity (i.e., HLA class I molecules, KIR and CD16A) are associated with this clinical variability, strengthening the essential role of cytotoxic lymphocytes in the immune control of HSV-1 (2). Polymorphisms of other genes, including APOE and CSSG-1, were related to susceptibility to recurrences, but their exact roles in HSV-1 control are unknown (1,44,45). In turn, inborn mutations of TLR3-IFN signaling pathway genes predisposing to herpetic encephalitis support a crucial role for TLR3 in the control of HSV-1 primary infection in the CNS (3), but those mutations are apparently not connected with common forms of HSV-1 infection.…”
Section: Discussionmentioning
confidence: 98%
“…We reported that a series of polymorphic key regulators at the interface of innate and adaptive immunity (i.e., HLA class I molecules, KIR and CD16A) are associated with this clinical variability, strengthening the essential role of cytotoxic lymphocytes in the immune control of HSV-1 (2). Polymorphisms of other genes, including APOE and CSSG-1, were related to susceptibility to recurrences, but their exact roles in HSV-1 control are unknown (1,44,45). In turn, inborn mutations of TLR3-IFN signaling pathway genes predisposing to herpetic encephalitis support a crucial role for TLR3 in the control of HSV-1 primary infection in the CNS (3), but those mutations are apparently not connected with common forms of HSV-1 infection.…”
Section: Discussionmentioning
confidence: 98%
“…In mice, chromosome 6 has been attributed to lethal disease via loci that are linked to the natural killer cell complex and tumor necrosis factor (42). The correlation of specific genetic loci with human disease, however, was reported only recently (36). In humans, mutations in Toll-like receptor 3 (TLR3)/UNC-93B have been linked to sporadic and recurrent cases of herpes simplex encephalitis in isolated families (10).…”
Section: Host Geneticsmentioning
confidence: 99%
“…A confounding observation is that the same region encodes both adenovirus and Coxsackie virus receptors. These efforts represent a first attempt to classify very complex relationships between clinical disease and the host genome (36).…”
Section: Host Geneticsmentioning
confidence: 99%
“…Symptoms that typically define orofacial herpes are an eruption of painful sores in and around the oral cavity. This includes lips (cold sores), cheeks, nose, chin, roof of the mouth, tongue, and gums (51). Symptoms that typically define ocular herpes include a clinically well-documented history of recurrent HSV-1 ocular disease (HSK), such as herpetic lid lesions, herpetic conjunctivitis, dendritic or geographic keratitis, stromal keratitis, decreased corneal sensation, and iritis consistent with HSK.…”
Section: Construction and Verification Of Hsv-1 And Hsv-2 Proteome MImentioning
confidence: 99%